O sujeito-colagem da estética contemporânea – antimoda jovem na UFRN - Azevedo, Virgínia Maria Borges de (2016)
Assuming the body as a space of communication and production of subjectivity, we investigate, through the perspective of the contemporary youth at UFRN, the complexity surrounding the act of adorning the body as an act of communication, more precisely a visual communication, filled with symbolism and personality. Using the metaporic method, we seek to follow the communicational act, resulting from the relationship between these unique individuals at UFRN, their adornments and clothing, as an act that produces meaning. Through these narratives and singular expression, observed in these adorned / dressed bodys, we were able to identify seven categories that outlines the collage-individual that we present here: Aesthetic inconsistency and frequent change of style, gender X clothes, spaces regulated by a dominant aesthetic, symbolic connection with garments and / or accessories, the building an authorial image through various aesthetic references, moment of aesthetic rupture with socially established standards, and, parts of the body whose modification or acceptance reflects aesthetic ruptures.